IMPLEMENTASI KOMPETENSI MAHASISWA MANAJEMEN DALAM PRATIK LOGISTIK GUDANG DI PT. INTITAMA BERLIAN PERKEBUNAN LEDO, KALIMANTAN BARAT - Agriandy, Afra; Dedy, Dedy (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2025)
Internship is a key component of the Merdeka Belajar Kampus Merdeka (MBKM) program, aiming to enhance students’ practical skills in real work environments. This article presents the internship experience of a Management student from Institut Shanti Bhuana in the warehouse logistics division of PT. Intitama Berlian Perkebunan, West Kalimantan. Over a four-month period, the student was involved in inventory receipt, recording, distribution, reporting, and other operational support tasks. The results show improved technical and soft skills, along with a deeper understanding of logistics management within the plantation industry.